El aprendizaje de conceptos científicos : aspectos epistemológicos, cognitivos y lingüísticos - Astolfi, Jean-Pierre (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper examines different aspects of topics dealt with over the last years by the team of Science Teaching in the INRP. Since this presentation is reconstructive, no claim for exhaustiveness is made.